Television as psychical object: Mad Men and the value of psychoanalysis for television scholarship. (September 2019) - Bainbridge, Caroline
Claims that Mad Men (2007–2015) is an obedient post-feminist text overlook the drama's images of both women and the history of feminism and its potential to impact on contemporary understandings of gender politics. Mad Men can be seen as a psychological object, helping viewers to explore links between their own experience and that of characters on screen as the narrative unfolds. Making links between the social re-emergence of feminist awareness, the drama's representations of second-wave feminism and a psychoanalytic understanding of mourning, I suggest that a return to psychoanalytic methodologies has the potential to enrich television scholarship.